Successful in vivo propagation of factor IX-producing hepatocytes in mice: Potential for cell-based therapy in haemophilia B - Tatsumi, Kohei; Ohashi, Kazuo; Kataoka, Miho; Tateno, Chise; Shibata, Masaru; Naka, Hiroyuki; Shima, Midori; Hisanaga, Michiyoshi; Kanehiro, Hiromichi; Okano, Teruo; Yoshizato, Katsutoshi; Nakajima, Yoshiyuki; Yoshioka, Akira (Thrombosis and Haemostasis, 2008)
Cell-based therapies using isolated hepatocytes have been proposed to be an attractive application in the treatment of haemophilia B due to the normal production of coagulation factor IX (FIX) in these particular cells. Current cell culture technologies have largely failed to provide adequate isolated hepatocytes, so the present studies were designed to examine a new approach to efficiently proliferate hepatocytes that can retain normal biological function, including the ability to synthesize coagulation factors like FIX. Canine or human primary hepatocytes were transplanted into urokinase-type plasminogen activatorsevere combined immunodeficiency (uPA/SCID) transgenic mice. Both donor hepatocytes from canines and humans were found to progressively proliferate in the recipient mouse livers as evidenced by a sharp increase in the circulating blood levels of species-specific albumin, which was correlated with the production and release of canine and human FIX antigen levels into the plasma. Histological examination confirmed that the transplanted canine and human hepatocytes were able to proliferate and occupy >80% of the host livers. In addition, the transplanted hepatocytes demonstrated strong cytoplasmic staining for human FIX, and the secreted coagulation factor IX was found to be haemostatically competent using specific procoagulant assays. In all, the results from the present study indicated that developments based on this technology could provide sufficient FIX-producing hepatocytes for cell-based therapy for haemophilia B.
Keywords: Haemophilia A/B; haemophilia therapy; coagulation factors; hepatology